Inhibition of the steroidogenic effects of cholera and heat-labile Escherichia coli enterotoxins by GM1 ganglioside: evidence for a similar receptor site for the two toxins. - Donta, S T (1975)
The effects of three different ganglioside preparations on cholera enterotoxin (CT) and heat-labile Escherichia coli enterotoxin (ECT)-induced steroidogenesis in Y1 and OS3 adrenal tumor cells in tissue culture were examined. Only with GM1 ganglioside was any inhibition of the toxins' effects noted. Concentrations of the crude ECT preparation that gave similar morphogenic and steroidogenic effects as CT were inhibited by the same amount or less of GM1 as that required to inhibit the effects of CT. The results of competition experiments also demonstrated that previous incubation of GM1 with one toxin could inhibit the ganglioside's ability to inactivate the other toxin. These findings indicate that at least for Y1 and OS3 adrenal tumor cells, GM1 may resemble or be the receptor for both CT and ECT.